Irreducible representation of finite metacyclic group of nilpotency class two of order 16 - Samin, Nizar Majeed (2013)
Representation theory is a study of real realizations of the axiomatic systems of abstract algebra. It originated in the study of permutation groups, and algebras of matrices. Representation theory has important applications in physics and chemistry. This research focuses on finite metacyclic groups. The classification of finite metacyclic groups is divided into three types which are denoted as Type I, Type II and Type III. For any group, the number of possible representative sets of matrices is infinite, but they can all be reduced to a single fundamental set, called the irreducible representations of the group. Irreducible representation is actually the nucleus of a character table and is of great importance in chemistry. In this research, the irreducible representation of finite metacyclic groups of class two of order 16 are found using two methods, namely the Great Orthogonality Theorem Method and Burnside Method